WRR dynamic resource allocation algorithm in visible light communication and WiFi heterogeneous network - Yang, Liwei; Liang, Xue; Fei, Yuang; Bi, Zeyang; Lv, Shusheng; Yang, Yating (Proceedings of ... IEEE International Conference on Computer and Communications (Online), 2023)
This paper proposes a weighted round-robin (WRR) algorithm based on the round-robin (RR) algorithm and proportional fairness (PF) algorithm aimed to enhance the quality of service (QoS) in visible light communication (VLC)/WiFi heterogeneous networks. Before each scheduling round, the algorithm assigns the user's priority based on the user's instantaneous request rate, distance to the nearest access point, and shadow fading. Meanwhile, user resource prioritization in different areas is proposed, considering the differences in VLC and WiFi coverage. Simulation results demonstrate that the WRR algorithm improves the system's throughput while maintaining fairness and can provide users with an improved communication experience, thereby increasing its application potential.